USING AN EIGEN VALUES AND SPATIAL FEATURES FOR BUILDING AN IRAQI LICENSE PLATE DETECTOR AND RECOGNIZER - Abood, Enas Wahab (International Journal of Research -GRANTHAALAYAH, 2017)
This paper produced a system for license plate recognition problem for Iraqi cars. The system depending on edges and position to locate license plate and character detection within it, for characters’ recognition an Eigen value for prepared templates was used to identify each character with template matching for recognizing government. Euclidian distance is invested for taking a decision; Experiments show that the recognition success was high and precise.